Hubungan Budaya Sekolah dengan Pro Environmental Behavior Siswa - Aisyah Andzari; Shahibah Yuliani; Dian Alfia Purwandari (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2021)
Abstract This study aims to obtain empirical data or facts that are actually true and reliable regarding the relationship between school culture and pro-environmental behavior in students. This research is motivated by the existence of a school culture that is useful for strengthening pro environmental behavior for students. The method used in this research is correlational quantitative method. The population used in this study were 351 grade 8 students of SMP Negeri 281 Jakarta, while the sample in this study amounted to 185 students. The research hypothesis was tested using Pearson Product Moment correlation analysis. The results of the analysis found that the school culture and students' pro environmental behavior were good. The results showed that there was a positive and strong relationship between school culture and pro environmental behavior among students of SMP Negeri 281 Jakarta.